A prognostic score to identify women at increased risk for abnormal uterine bleeding during anticoagulation for venous thromboembolism, - Gabrielle Sarlon-Bartoli; Juan Criado; Saskia Middeldorp; José Antonio Nieto; María del Carmen Díaz-Pedroche; Farès Moustafa; Nuria Ruiz-Giménez; Benjamin Brenner; Manuel Monreal; Pierpaolo DI Micco; the RIETE Group; Bosevski, Marijan; et al. (Elsevier, 2023)
Introduction Little is known about the clinical characteristics of women at increased risk for abnormal uterine bleeding (UB) during anticoagulation for venous thromboembolism (VTE). Methods We used the RIETE registry to identify the baseline characteristics of women developing abnormal UB during anticoagulation. We used logistic regression analysis to identify independent predictors for abnormal UB. Then, we built a prognostic score to identify at-risk women. Results From March 2001 through October 2022, there were 54,372 women with VTE. During anticoagulation (median, 181 days), 318 (0.6%) developed abnormal UB (major bleeding = 88, clinically relevant non-major (CRNM) = 230). On multivariable analysis, women aged <50 years, weighing >70 kg, with uterine cancer, recent UB, anemia, estrogen-related VTE, or receiving rivaroxaban or apixaban were at increased risk for abnormal UB. Using the prognostic score, 42,273 women (78%) were at low-risk, 8,828 (16%) intermediate-, and 3,271 (6.1%) at high-risk for abnormal UB. Their rates of abnormal UB were: 0.28 (95%CI: 0.23–0.35), 1.32 (95%CI: 1.07–1.61) and 7.12 (95%CI: 5.98–8.41) bleeds per 100 patient-years, respectively. The c-statistic was 0.80 (95%CI: 0.77–0.83). The rates of major UB were: 0.06 (95%CI: 0.04–0.09), 0.43 (95%CI: 0.30–0.60) and 1.85 (95%CI: 1.31–2.53) per 100 patient-years, respectively (c-statistic: 0.84; 95%CI: 0.80–0.89). The rates of CRNM uterine bleeding were: 0.21 (95%CI: 0.17–0.26), 0.85 (95%CI: 0.65–1.08), and 5.02 (95%CI: 4.09–6.10) bleeds per 100 patient-years, respectively (c-statistic: 0.78; 95%CI: 0.75–0.82). Conclusions Using 7 variables easily available at admission, we built a prognostic score that reliably identified women with VTE at increased risk for abnormal UB during anticoagulation.
Keywords: Anticoagulants; Venous thromboembolism; Uterine bleeding; Prognostic score